Slum upgrading in the ABC Region in the context of Programa de Aceleração do Crescimento- -Urbanização de Assentamentos Precários - Denaldi, Rosana (2016)
This paper analyzes interventions in slums located in the ABC Region (State of São Paulo, Brazil) that have been financed in the context of Programa de Aceleração do Crescimento – Urbanização de Assentamentos Precários (PAC-UAP). Through this program, financial resources aimed at the upgrading of 49 precarious settlements (slums) are allocated to this region. The research shows evidence of low efficiency in the implementation of projects. Our characterization of the settlements and interventions provides a general panorama of the program’s implementation and its bottlenecks. It is concluded that, to understand the lack of efficiency in slum upgrading, it is important to understand the characteristics of these territories, the nature of interventions, the regulation and operationalization of the program, and the institutional limitations of municipal governments.